Analysis of Morphological Traits, Cannabinoid Profiles, THCAS Gene Sequences, and Photosynthesis in Wide and Narrow Leaflet High-Cannabidiol Breeding Populations of Medical Cannabis - Murovec, Jana; Eržen, Jan Jurij; Flajšman, Marko; Vodnik, Dominik (Frontiers in Plant Science, 2022)
Cannabis sativa L. is one of the oldest cultivated crops, used in medicine for millennia due to therapeutic characteristics of the phytocannabinoids it contains. Its medicinal properties are highly influenced by the chemotype, that is, the ratio of the two main cannabinoids cannabidiol (CBD) and Δ-9-tetrahydrocannabinol (THC). Based on published data, the chemotype should correlate with plant morphology, genetics, and photosynthetic properties. In this work, we investigated leaf morphology, plant growth characteristics, cannabinoid profiles, THCAS gene sequences, and plant photosynthetic traits in two breeding populations of medical cannabis (MX-CBD-11 and MX-CBD-707). The populations differed significantly in morphological traits. The MX-CBD-11 plants were taller, less branched, and their leaves had narrower leaflets than the bushier, wideleaved MX-CBD-707 plants, and there were significant differences between populations in the dry biomass of different plant parts. Based on these morphological differences, MX-CBD-11 was designated as a narrow leaflet drug type or vernacular "Sativa" type, while MX-CBD-707 was classified as wide leaflet drug type or "Indica" type. Chemical characterisation revealed a discrepancy between the expected chemotypes based on plant morphology;although both populations have high CBD, within each Type II (CBD/THC intermediate) and Type III (CBD dominant) plants were detected. The THCAS gene sequence analysis clustered the plants based on their chemotypes and showed high similarity to the THCAS sequences deposited in NCBI. In silico complementary analysis, using published molecular markers for chemotype determination, showed their low discrimination power in our two populations, demonstrating the genotype dependence of the molecular markers. Basic photosynthetic traits derived from light and CO2 response curves were similar in the populations. The results of this study showed that based on visual appearance and some morphological measurements, it is not possible to determine a plant’s chemotype. Visually homogenous plants had different cannabinoid profiles and, vice versa, morphologically distinct plants contained similar CBD and THC content. The two chemotypes identified in our experimental plants therefore did not correlate with plant visual appearance, leaf morphometry, and photosynthetic properties of the populations studied. Correlation was only demonstrated with the respect to THCAS sequences, which showed great discrimination power between the chemotypes.